The Healing Organization - Sally Robertson; Laura Edmunds (Academic Chairpersons Conference Proceedings, 2023)
How do we transform our organizations into spaces of community, wellness, collaboration, and safety? Looking at the entire campus as “The Healing Organization” we focus on human-centered leadership practices to create a better future for our departments and our classrooms.
Keywords: Leadership wellness; wholistic healing; campus culture; success; change; positive disruption